2021
DOI: 10.3390/genes12010120
|View full text |Cite
|
Sign up to set email alerts
|

HEDGEHOG/GLI Modulates the PRR11-SKA2 Bidirectional Transcription Unit in Lung Squamous Cell Carcinomas

Abstract: We previously demonstrated that proline-rich protein 11 (PRR11) and spindle and kinetochore associated 2 (SKA2) constituted a head-to-head gene pair driven by a prototypical bidirectional promoter. This gene pair synergistically promoted the development of non-small cell lung cancer. However, the signaling pathways leading to the ectopic expression of this gene pair remains obscure. In the present study, we first analyzed the lung squamous cell carcinoma (LSCC) relevant RNA sequencing data from The Cancer Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Univariate and multivariate analysis showed that PRR11 was an independent prognostic factor for squamous cell carcinoma of the tongue [24]. In accordance with the TCGA database, the present study found that PRR11 had a significant effect on the survival rate of osteosarcoma, and the Regarding the mechanism by which PRR11 promotes tumor progression, many bioinformatics studies have shown that PRR11 is mainly involved in regulation of the cell cycle, M phase, and mitotic cell cycle, and in various tumor signaling pathways [25][26][27]. In addition, a large number of cell experiments have also shown that PRR11 affects cell migration, proliferation, and invasion in a variety of tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Univariate and multivariate analysis showed that PRR11 was an independent prognostic factor for squamous cell carcinoma of the tongue [24]. In accordance with the TCGA database, the present study found that PRR11 had a significant effect on the survival rate of osteosarcoma, and the Regarding the mechanism by which PRR11 promotes tumor progression, many bioinformatics studies have shown that PRR11 is mainly involved in regulation of the cell cycle, M phase, and mitotic cell cycle, and in various tumor signaling pathways [25][26][27]. In addition, a large number of cell experiments have also shown that PRR11 affects cell migration, proliferation, and invasion in a variety of tumors.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, the transcriptional regulatory mechanisms of SKA2 gene were investigated, previous studies revealed that some transcription factors such as NF-Y (nuclear transcription factor Y), CREB (cyclic AMP responsive element-binding protein), NF-κΒ, and p53, non-coding RNAs including miR-301, miR-141 and Circ_0008039, and Hedgehog pathway member GLI1/2, are implicated in dysregulation of SKA2 expression and contributed to tumor development [11,[14][15][16][17][18]. Nevertheless, downstream genes regulated by SKA2 in cancer cells are still vacant.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Taken together, aberrant expression of SKA2 is associated with tumor progression. Additionally, the transcriptional regulatory mechanisms of SKA2 gene were investigated, previous studies revealed that some transcription factors such as NF-Y (nuclear transcription factor Y), CREB (cyclic AMP responsive element-binding protein), NF-κΒ, and p53, non-coding RNAs including miR-301, miR-141 and Circ_0008039, and Hedgehog pathway member GLI1/2, are implicated in dysregulation of SKA2 expression and contributed to tumor development 11 , 14 - 18 . Nevertheless, downstream genes regulated by SKA2 in cancer cells are still vacant.…”
Section: Introductionmentioning
confidence: 99%